أثر التحول الرقمي والتكنولوجيا المالية على زيادة تنافسية المؤسسات الاقتصادية دراسة حالة مؤسسة بريد الجزائر - خبزي سمية; مليكة قسوم; فاطمة الزهرة دندوقي (جامعة الوادي University of Eloued, 2025)
تهدف هذه الدراسة الى إبراز ما مدى مساهمة التحول الرقمي والتكنولوجيا المالية في دعم تنافسية المؤسسات الاقتصادية-دراسة حالة مؤسسة بريد الجزائر بولايتي المغير وتقرت-، ومن أجل بلوغ هذا الهدف تم الاعتماد على المنهج الوصفي في الفصل النظري، حيث تطرقنا نظريا للتحول الرقمي والتكنولوجيا المالية وتنافسية المؤسسات الاقتصادية، وكذلك تم الاعتماد على المنهج التحليلي في دراسة الحالة حيث تم توزيع استبيان على (138) موظفا وموظفة في المؤسسات محل الدراسة وتم الاعتماد على برنامج "SPSS.V27" في تحليل النتائج ؛ وكان من أبرز نتائجها هي وجود تأثير معنوي ذو دلالة إحصائية لأثر التحول الرقمي والتكنولوجيا المالية على زيادة تنافسية المؤسسات محل الدراسة عند مستوى الدلالة (α≤ 0.05) وأن التحول الرقمي هو المتغير الأكثر تأثيرًا وله دلالة إحصائية قوية على تحسين التنافسية. وخلصت الدراسة إلى مجموعة من التوصيات والاقتراحات أهمها: دعم البنى التحتية الرقمية والأنظمة الذكية بما يضمن مرونة العمليات وسرعة الأداء وتعزيز ثقة المستخدمين في المدفوعات والتحويلات الرقمية This study aims to highlight the extent to which digital transformation and financial technology contribute to enhancing the competitiveness of economic institutions, through a field study of a sample of postal institutions in the provinces of El Meghair and Touggourt. To achieve this goal, the descriptive approach was adopted in the theoretical chapter, where we theoretically addressed digital transformation, financial technology, and the competitiveness of economic institutions. The analytical approach was also adopted in the case study, where a questionnaire was distributed to (138) male and female employees in the institutions under study. The results were analyzed using the SPSS.V27 program. A statistically significant effect of the impact of digital transformation and financial technology on increasing the competitiveness of the institutions under study was found at the significance level (α≤ 0.05) and that digital transformation is the most influential variable and has a strong statistical significance in improving competitiveness. The study concluded with a set of recommendations and suggestions, the most important of which are: supporting digital infrastructure and smart systems to ensure operational flexibility and speed of performance and enhance user confidence in digital payments and transfers.
ماستر علوم التسيير
Keywords: تحول رقمي; تكنولوجيا مالية; تنافسية مؤسسات إقتصادية; مؤسسة اقتصادية; بريد جزائر; Digital transformation; Financial technology; Competitiveness; Economic institution; Algeria Post.